2010
DOI: 10.1590/s0102-695x2010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Atividade citotóxica e antiangiogênica de Punica granatum L., Punicaceae

Abstract: RESUMO:Punica granatum L., Punicaceae, amplamente usada no Brasil, foi avaliada quanto ao seu potencial antitumoral in vitro e in vivo. Investigou-se in vitro a citotoxicidade do extrato etanólico do fruto e folha da P. granatum utilizando células K-562 e células do Tumor Ascítico de Ehrlich (TAE), pelos métodos de redução do MTT e exclusão do azul de tripano. Nos estudos in vivo avaliou-se o aumento da sobrevida de animais portadores do TAE e tratados, por via oral, com diferentes doses dos extratos etanólico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
6
0
14
Order By: Relevance
“…Punica granatum L. (romã), da família Punicaceae, é uma planta exótica originária do Oriente Médio e amplamente distribuída no Brasil 27,28 . É conhecida por ter ação farmacológica antimicrobiana, antioxidante, antitumoral e cicatrizante, conforme demonstrado em diversos estudos [28][29][30][31] . Na odontologia, é eficaz contra adesão de microrganismos cariogênicos, entre eles as bactérias Streptococcus mitis, S. mutans, S. sanguis, S.…”
Section: Resultsunclassified
“…Punica granatum L. (romã), da família Punicaceae, é uma planta exótica originária do Oriente Médio e amplamente distribuída no Brasil 27,28 . É conhecida por ter ação farmacológica antimicrobiana, antioxidante, antitumoral e cicatrizante, conforme demonstrado em diversos estudos [28][29][30][31] . Na odontologia, é eficaz contra adesão de microrganismos cariogênicos, entre eles as bactérias Streptococcus mitis, S. mutans, S. sanguis, S.…”
Section: Resultsunclassified
“…In recent years, it has been found that pomegranate peel has antidiabetic, antiviral, anticarcinogenic, and antibacterial properties [6]. Pomegranate peels, used for wound healing, blood arresters, diarrhea inhibitors, skin infections, and viral diseases in the field of traditional medicine, are also used in the compositions of recommended drugs for various health disorders such as antimicrobial, antitumoral, antiinflammatory, and antiulcer drugs, as well as for diabetes and genital infections, thanks to the studies carried out in recent years [7][8][9][10][11][12][13][14]. There are important phenolic compounds such as tannins (punicalagin, punicalin, elagic acid, and gallic acid) and flavanoids (catechin, anthocyanin, and other complex flavanoids) in parts of the pomegranate peel [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used parameters to evaluate cellular changes is cell viability, which can be visualized using vital dyes suc h as neutral red or Try pan blue (Rogero et al, 2003;Oliveira et al, 2010). The main objective of in vitro cytotoxicity assays is to facilitate the study of cell behavior in a controlled environment free of the complexity of the living organism and in an easy, fast, and inexpensive way (Martins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%